Interventions supporting baccalaureate achievement of Latinx STEM students matriculating at 2‐year institutions: A systematic review. Issue 4 (2nd October 2018) - Martin, Julie P.; Choe, Nathan Hyungsok; Halter, Jared; Foster, Margaret; Froyd, Jeffrey; Borrego, Maura; Winterer, Erica R.
Abstract: Numerous national reports have identified the importance of significantly improving pathways that begin with Latinx students enrolling in 2‐year institutions and ultimately completing baccalaureate degrees in STEM fields at 4‐year institutions. Many programs using multiple interventions have been designed, implemented, and studied to achieve this goal. To synthesize what has been learned from studies of these programs, this article presents a systematic review of published studies of programs designed to support Latinx student success in 2‐year institutions and successful transfer to 4‐year institutions, particularly for STEM majors. A total of 49 quantitative, 9 qualitative, and 16 mixed‐methods studies published as reports, articles, or dissertations since 1980 were identified that met the criteria for the review. Studies covered a wide range of interventions, including mentoring, counseling, advising, study groups, tutoring, scholarships, orientations, career services, undergraduate research, articulation agreements, and transfer programs. Individually, these studies report positive influences on student success outcomes, including 2‐ and 4‐year graduation, transfer to a 4‐year institution, retention, and success in individual courses. However, the number of qualifying studies was surprisingly small, considering the importance of improving success of Latinx students and the length of time during which the problem has been repeatedly emphasized. Few interventions have been undertaken from explicitly assets‐based perspectives or theoretical frameworks. The lack of explicit frameworks underlying interventions—combined with a sole/primary focus on students—suggests many interventions were approached from a deficit‐based perspective. Further, the study found no pattern of replication studies that might confirm effectiveness of potentially promising interventions. Based on our analysis of evaluations presented in the studies, it does not appear that the research community has developed agreed‐upon methods to evaluate commonly agreed‐upon outcomes. Finally, no intervention has been sufficiently supported that widespread implementation could be recommended.